Thermal and Acidic Treatments of Gluten Epitopes Affect Their Recognition by HLA-DQ2 in silico - Gao, Jihui; Du, Haolan; Zhou, Zekun; Liang, Zhongxin; Liang, Hongrui; Zhang, PeiAo; Wei, Xue; Liu, Shujun; Fu, Linglin; Wang, Yanbo; Che, Huilian; Xue, Wentong; et al. (Frontiers in Nutrition, 2021)
Celiac disease (CD) is a prevalent disorder with autoimmune features. Dietary exposure of wheat gluten (including gliadins and glutenins) to the small intestine activates the gluten-reactive CD4+ T cells and controls the disease development. While the human leukocyte antigen (HLA) is the single most important genetic factor of this polygenic disorder, HLA-DQ2 recognition of gluten is the majority biological step among patients with celiac disease. Gluten epitopes are often rich in Pro and share similar primary sequences. Here, we simulated the solution structures changes of a variety of gluten epitopes under different pH and temperatures, to mimic the fermentation and baking/cooking processes. Based on the crystal structure of HLA-DQ2, binding of differently processed gluten epitopes to DQ2 were studied in silico. This study revealed that heating and pH change during the fermentation process impact the solution structure of gluten epitope. However, detailed response of each immunogenicity to different treatment mainly depended on the primary amino acid sequence of each GEP, especially acidic amino acid residues that playing a pivotal role in their recognition by HLA-DQ2.